The Role of Autophagy in Osteoarthritis - Duan, Ran; Xie, Hui; Liu, Zheng-Zhao (Frontiers in Cell and Developmental Biology, 2020)
Chondrocytes are the only cell type in normal cartilage. The pathological changes of osteoarthritis (OA) mostly revolve around the apoptosis and dysfunction of chondrocytes. Autophagy, as an intracellular degradation system that maintains the steady state of energy metabolism in cells, has been shown to restore the function of damaged chondrocytes, alleviating the occurrence and progression of OA. In this review, we explored the relationship between autophagy and OA and the key molecules of autophagy pathway that regulate the progression of OA, providing new ideas for OA treatment by targeting autophagy.